Navigating Governance: ESOP, Regulations, and Corporate Governance Quality: Menavigasi Tata Kelola: ESOP, Peraturan, dan Kualitas Tata Kelola Perusahaan - Sarwenda Biduri; Anik Maulidiya; Wiwit Hariyanto (Universitas Muhammadiyah Sidoarjo, 2021)
This study investigates the impact of Employee Stock Ownership Program (ESOP) and regulatory factors on the quality of corporate governance implementation within Indonesian public companies. Utilizing quantitative methods and primary data, the research focuses on a sample of 55 observations from 11 companies over five periods, chosen through purposive sampling from a population of 156 companies ranked by the Indonesian Institute for Corporate Governance (IICG) during 2013-2017. Employing multiple linear regression, t-tests, F-tests, and coefficient of determination analysis through SPSS software, the findings reveal that while ESOP does not exert a partial influence, regulatory factors significantly affect the quality of corporate governance implementation. Furthermore, both ESOP and regulatory factors collectively demonstrate an influencing role in shaping the quality of corporate governance implementation. These results contribute to enhancing the understanding of the interplay between ownership programs and regulatory influences on corporate governance practices, bearing implications for governance policies and strategic decision-making.Highlight: ESOP's Limited Influence: The study finds that Employee Stock Ownership Program (ESOP) doesn't partially impact corporate governance quality, shedding light on the complexities of ownership incentives. Regulatory Impact: Regulatory factors emerge as a significant driver of corporate governance quality, underscoring the importance of legal frameworks in shaping governance practices. Collective Influence: Both ESOP and regulatory factors collectively play a crucial role in shaping corporate governance quality, highlighting the need for a comprehensive approach to governance enhancement. Keyword: ESOP, Regulatory Factors, Corporate Governance, Quantitative Analysis, Ownership Programs.